STUDI KORELASI PERILAKU ADAPTIF DAN KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR PADA SISWA UNDERACHIEVER DI BALI - Carina, Tiara; Supriyadi, Supriyadi (Jurnal Psikologi Udayana; Vol 3 No 1 (2016), 2016)
Education is an effort that deliberately, regularly runs and plans to modify or develop behavior which the environment wish for (Wahyuningsih, 2004). There are several problem in education, which is some students have learning difficulties. Student with above average level of intelligence but low achieving at school is called by underachiever. Academic achievement is result of learning processes that shown from the changes on knowledge and comprehension, value, attitude, and skill (Winkle, 1997). According to Suryabrata, Shertzer, and Stone (in Winkle, 1997), there are some psychological factors that influence academic achievement. Psychological factors that were studied in this research are adaptive behavior and emotional intelligence. This research is quantitative study using double regression technique. Subjects of this research are 47 underachiever students (n boys = 24; n girls = 23) who their age are between 11 to 15 year old. The sampling method is random cluster sampling. The data collection method uses Adaptive Behavior Scale (rxx = 0.983), Emotional Intelligence Scale (rxx = 0.870), and study report in odd semester. From hypothesis test with double regression technique, it is found that the correlational coefficient is 0.857, the regression coefficient is 0.735, the significant coefficient of the regression is 0.000, and the significant coefficient of independent variables are both 0.000 and 0.043. It shows that there is significant causal correlation between adaptive behavior and emotional intelligence with academic achievement, the adaptive behavior and emotional intelligence influences academic achievement as 73.5%. Keywords: adaptive behavior, emotional intelligence, academic achievement, underachiever